134k views
22 votes
Solve for x

2x3=x2+6x

please help me. Thanks

1 Answer

8 votes

Answer:

heya! ^^


2x {}^(3) = x {}^(2) + 6x \\ \\ 2x {}^(3) = x(x + 6) \\ \\ dividing \: both \: sides \: by \: x \\ \\ \frac{2\cancel{x} {}^(3) }{\cancel{x}} = \frac{\cancel{x}(x + 6)}{\cancel{x}} \\ \\ 2x {}^(2) = x + 6 \\ \\ 2x {}^(2) - x - 6 = 0 \\ \\ by \: splitting \: the \: middle \: term \: ( - x) \\ \\ 2x {}^(2) - 4x + 3x - 6 = 0 \\ \\ 2x(x - 2) + 3(x - 2) = 0 \\ \\ 2x + 3 = 0 \: \: \: or \: \: \: (x - 2) = 0 \\ \\ x = ( - 3)/(2) \: \: \: \: or \: \: \: \: x = 2

hope helpful :D

User Michael Herrmann
by
5.5k points